An in vitro evaluation of graphene oxide reduced by Ganoderma spp. in human breast cancer cells (MDA-MB-231) - Gurunathan, Sangiliyandi (Dove Medical Press, 2014)
BACKGROUND: Recently, graphene and graphene-related materials have attracted much attention due their unique properties, such as their physical, chemical, and biocompatibility properties. This study aimed to determine the cytotoxic effects of graphene oxide (GO) that is reduced biologically using Ganoderma spp. mushroom extracts in MDA-MB-231 human breast cancer cells. METHODS: Herein, we describe a facile and green method for the reduction of GO using extracts of Ganoderma spp. as a reducing agent. GO was reduced without any hazardous chemicals in an aqueous solution, and the reduced GO was characterized using a range of analytical procedures. The Ganoderma extract (GE)-reduced GO (GE-rGO) was characterized by ultraviolet-visible absorption spectroscopy, X-ray diffraction, Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, dynamic light scattering, scanning electron microscopy, Raman spectroscopy, and atomic force microscopy. Furthermore, the toxicity of GE-rGO was evaluated using a sequence of assays such as cell viability, lactate dehydrogenase leakage, and reactive oxygen species generation in human breast cancer cells (MDA-MB-231). RESULTS: The preliminary characterization of reduction of GO was confirmed by the red-shifting of the absorption peak for GE-rGO to 265 nm from 230 nm. The size of GO and GE-rGO was found to be 1,880 and 3,200 nm, respectively. X-ray diffraction results confirmed that reduction processes of GO and the processes of removing intercalated water molecules and the oxide groups. The surface functionalities and chemical natures of GO and GE-rGO were confirmed using Fourier-transform infrared spectroscopy and X-ray photoelectron spectroscopy. The surface morphologies of the synthesized graphene were analyzed using high-resolution scanning electron microscopy. Raman spectroscopy revealed single- and multilayer properties of GE-rGO. Atomic force microscopy images provided evidence for the formation of graphene. Furthermore, the effect of GO and GE-rGO was examined using a series of assays, such as cell viability, membrane integrity, and reactive oxygen species generation, which are key molecules involved in apoptosis. The results obtained from cell viability and lactate dehydrogenase assay suggest that GO and GE-rGO cause dose-dependent toxicity in the cells. Interestingly, it was found that biologically derived GE-rGO is more toxic to cancer cells than GO. CONCLUSION: We describe a simple, green, nontoxic, and cost-effective approach to producing graphene using mushroom extract as a reducing and stabilizing agent. The proposed method could enable synthesis of graphene with potential biological and biomedical applications such as in cancer and angiogenic disorders. To our knowledge, this is the first report using mushroom extract as a reducing agent for the synthesis of graphene. Mushroom extract can be used as a biocatalyst for the production of graphene.